2014
DOI: 10.1097/scs.0000000000000762
|View full text |Cite
|
Sign up to set email alerts
|

Calvarial Thickness and Diploic Space Development in Children With Sagittal Synostosis as Assessed by Computed Tomography

Abstract: Following surgical management of craniosynostosis, residual calvarial defects may require reconstruction, frequently with the use of cranial bone grafts. Knowledge of optimal sites for harvest would be beneficial in such situations. The goal of this study is to compare calvarial thickness (CALV) and diploic thickness (DIPL) in children with corrected sagittal synostosis to normal controls (n = 47) using postoperative CT scans. We also compare the results from children who had undergone open (OPEN) (n = 26) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Furthermore, a deeper understanding of bone microstructure in infants with sagittal synostosis could have implications for other craniofacial techniques 26 such as helmet therapy 30 and distraction osteogenesis, 31 all of which rely on the malleability of infant cranial bone to achieve desirable head shape changesdwhich, as shown in this study, inherently depend on the bone. Given the different surgical treatments available for the correction of sagittal synostosis, 4,5,32e35 future studies relating skull bone to surgical outcomes could help determine the optimal type of surgical intervention for each patient.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, a deeper understanding of bone microstructure in infants with sagittal synostosis could have implications for other craniofacial techniques 26 such as helmet therapy 30 and distraction osteogenesis, 31 all of which rely on the malleability of infant cranial bone to achieve desirable head shape changesdwhich, as shown in this study, inherently depend on the bone. Given the different surgical treatments available for the correction of sagittal synostosis, 4,5,32e35 future studies relating skull bone to surgical outcomes could help determine the optimal type of surgical intervention for each patient.…”
Section: Discussionmentioning
confidence: 83%
“…mCT cannot obviously be used to assess patients preoperatively; hence, some of the parameters analysed here cannot be retrieved for patients. However, cranial thickness can be measured from CT head scans 25,26 or noninvasively using ultrasound techniques 27e29 and therefore could be used to plan surgery accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cranial bone density and size changes rapidly due to growth during the early years of life. The cranial bone volume doubles in size by the first 6 months, triples by 2.5 years of age, and is 90% complete by 5 years of age 35,36 . Despite manually choosing a participant‐specific signal threshold, a signal intensity–based approach iMR performed poorly in segmenting bone, particularly in younger participants (Figure 2(D)).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of brain/head development, pediatric patients have rapid changes in cortical bone density, size, and tissue MR properties in the first years of their life. 35,36 MR scans should be performed as soon as possible after the CT scans. Due to MR scanner availability and the patient's schedule, we allow a time interval between CT and MR.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Some authors have reported a non-regeneration of the total thickness of the total parietal bone thickness after graft harvesting in adults (Chang et al, 2014;Touzet et al, 2011). The case is different with children, who usually present with total regeneration of skull bone after graft harvesting (Barone and Jimenez, 1997;Ghosh et al, 2014). Removing bone from the parietal area decreases the thickness of the calvarium definitively and may potentially affect the skull's mechanical strength.…”
Section: Introductionmentioning
confidence: 99%